If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -1(-8) = 3n Multiply -1 * -8 n + 8 = 3n Reorder the terms: 8 + n = 3n Solving 8 + n = 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 8 + n + -3n = 3n + -3n Combine like terms: n + -3n = -2n 8 + -2n = 3n + -3n Combine like terms: 3n + -3n = 0 8 + -2n = 0 Add '-8' to each side of the equation. 8 + -8 + -2n = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -2n = 0 + -8 -2n = 0 + -8 Combine like terms: 0 + -8 = -8 -2n = -8 Divide each side by '-2'. n = 4 Simplifying n = 4
| 4x-4+5+(x+8)=0 | | 10+0.25(200)=X | | 8+7m=m-4 | | 10-(x-7)+2x=5 | | r^2-3=2r | | 2=-2b-8 | | -17+3(.25)=x | | 6n-3=4+5n | | 4g=5 | | X^2+5x-24=-6+2x | | 10+X=-30 | | (X+6)(X-8)(2x-7)=0 | | -8(t+9)=6 | | 3x-1+4x+3=180 | | 5b^2+31b+30=0 | | y^2-4x^2=16 | | 6=7s-4 | | 2+2p=2-2p | | 1.82=Log(x) | | 2(-4)-3=x | | 5x+4=6x-42+8 | | 7+m=6 | | 2p+4p-7x+3=4p+5-3x | | -5x-6=-1 | | V^2-2v-5=-3v-3 | | 12x-8=15x-14 | | -5(x-3)=5(x-3) | | 5m+3n-2m-8n= | | (x+2)(7x+8)=0 | | 9-4+5h+3x= | | 9x/2=3x | | 9-4+53+32= |